2016
DOI: 10.1039/c6ta02348g
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched grafting enabling simultaneous enhancement of the boric acid uptake and the adsorption rate of a complexing membrane

Abstract: Hyperbranched polyols were grafted onto a PAN membrane via a two-step process for boron removal. The grafted hyperbranched scaffold was utilized to optimize the ligand distribution so that a complexing membrane with both high capacity and high adsorption rate was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…Boric acid -carbohydrate interactions are well known [32]; although a stronger complex is formed at basic pH than at acidic pH, equilibrium between the boric acid and the borate ester is present. While such experimental evaluation was not performed in this work, it has recently been well documented, including for membranes [33,34]. The residence time of boron on each binding site may be a reasonable explanation for the boron rejection.…”
Section: Boron Rejectionmentioning
confidence: 94%
“…Boric acid -carbohydrate interactions are well known [32]; although a stronger complex is formed at basic pH than at acidic pH, equilibrium between the boric acid and the borate ester is present. While such experimental evaluation was not performed in this work, it has recently been well documented, including for membranes [33,34]. The residence time of boron on each binding site may be a reasonable explanation for the boron rejection.…”
Section: Boron Rejectionmentioning
confidence: 94%
“…The boric acid could reversibly adsorb and desorb from the surface of the chitosantannic acid functional paper by formation and dissociation of borate with catechol at pH = 10 and pH = 4, respectively (Scheme 1). The adsorption ability was superior to most other studies (Erdem et al 2013;Meng et al 2016;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 56%
“…Adsorbents have been reported for the selective adsorption of boric acid after complexing with the hydroxyl of boric acid; these are resistant to interference by the coexisting salts during adsorption (Meng et al 2016;Lyu et al 2017;Sun et al 2018) However, most of these adsorbents mainly focus on the use of anion-exchange resin, activated carbon, and magnetic sorbents as carriers, and these carriers usually involve sophisticated preparation processes, complicated structures, and are expensive. This limits their application in the removal of boric acid.…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, the adsorption kinetics of boric acid on the affinity membrane is mainly affected by boron diffusion between layers of the polyhydroxy copolymer on the surface of the affinity film and the interaction between boric acid and hydroxyl functional groups. Meng et al [19] pointed out that the hyperbranched polymer scaffold is beneficial to superior boron-uptake performance.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the ligand structures of polyhydroxy polymers, Du et al [18] found that the presence of the amino group and the branched chain structure are beneficial to improve the complexing efficiency. Recently, hyperbranched-polyol-tethered membranes were proved to be highly effective and fast adsorbent, but their preparation conditions are more demanding [19,20].…”
Section: Introductionmentioning
confidence: 99%